Implicature in John Green’s The Fault Of Our Stars - Nanda, Dheril Sofia (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2015)
Discourses on revealing meanings in utterances are widely discussed in some fields of linguistics, semantics, presupposition, and implicature. This study is an example of how implicature is employed in a novel, which is a depiction of real life conversation. The aims of this study are to reveal the use of implicature in a novel by using Grice’s cooperative principle framework and to entangle the implied meanings in the conversations in terms of their maxim arrangement. Qualitative research design was used in this study. The result of the study shows that there are two kinds of implicature, namely generalized and particularized conversational implicature. It is also found that there are five patterns of maxims organization in generalized conversational implicatures and four patterns of maxims organization in particularized conversational implicatures.